An atom/molecule/DNA probing and transportation using dynamic optical tweezers via a wavelength router - Vongchumyen, C.; Tasakorn, M.; Mitatha, S.; Yupapin, P. P. (My University, 2011)
A dark soliton pulse beam that has potential applications in the probing and transport of atoms or molecules as an optical tweezers is demonstrated. The trapped pulse beam is formed in the gap between a BP signal at 1500.00 nm and Stokes signal at 1500.09 nm, which has peak powers of -12 dBm. The generated beam is seen to be stable with no fluctuations over a test period of 10 min, which is important to ensure that the transported atom/molecule is not lost in the link media, therefore, the dynamic optical tweezers are now plausible. The theoretical background of the trapped atom/molecule is also analyzed and described in details. The atomic/molecular network via a wavelength router is also described. © 2010 Elsevier GmbH All rights reserved.
Keywords: Atom transportation; DNA transportation; Dynamic tweezers; Wavelength router